Sustainable internal transport barrier discharge at KSTAR. (16th November 2021) - Chung, J.; Hahn, S.-H.; Han, H.; Kang, J.; Kim, H.S.; Jeon, Y.M.; Ko, J.; Lee, K.D.; Ko, W.H.; Seo, S.H.; Lee, J.H.; Juhn, J.-W.; et al.
Abstract: We explore the inboard-limited internal transport barrier (ITB) as an alternative advanced operation scenario for KSTAR. This paper presents in detail the progress of the ITB experiment at KSTAR. In an earlier study, the ITB formed in both ion and electron thermal channels, and an early neutral-beam injection (NBI) power of over 4 to 5 MW under a limited L-mode was crucial to ITB access. In the present study, we access the ITB experimentally with about 3 MW of NBI power by using the upper single null (USN), which is an unfavorable H-mode condition with a higher L–H power threshold. Finding an ITB access condition with a lower heating power should allow for a more efficient control of the heat flux and for maintaining stable plasma performance. The key control parameters of the experiment are the vertical position and the location of outboard striking point of the plasma. The shape-control attempts to divert the plasma to a vertically shifted USN with a marginal touch of the inboard limiter so that the plasma can remain in the L-mode at the boundary, while the striking-point control maintains the ITB performance for a longer period of time.